ENTREPRENEURIAL RISK MANAGEMENT PRACTICES ADOPTED BY SMALL AND MEDIUM SCALE ENTREPRENEURS FOR SUCCESSFUL BUSINESS OPERATIONS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained entrepreneurial risk management practices adopted by small and medium scale entrepreneurs (SMEs) for successful business operations in Anambra State. Two research questions guided the study and two null hypotheses were tested. Descriptive survey research design was adopted for the study. The population comprised 1,813 registered SMEs managers in Anambra State. A sample of 362 managers of SMEs was used through simple random sampling technique. The instrument for data collection was on 18-item structured questionnaire. The instrument was validated by three experts. To determine the internal consistency of items in the instrument, Cronbach Alpha was used and reliability co-efficient values of 0.87 and 0.89 for clusters B1 and B2 with an overall co-efficient value of 0.88 were obtained. Mean and standard deviation were used to answer the research questions, while t-test was used to test the null hypotheses at 0.05 alpha level. The findings of the study revealed that SMEs managers lowly adopted risk identification practices for their business operations in Anambra State, while they moderately adopted risk communication practices. SMEs managers differed significantly in their mean ratings on the extent they adopt risk identification practices for their business operations in Anambra State, Nigeria based on gender. They did not significantly differ in their mean ratings on the adoption of risk communication practices for their business operations. The study concluded that entrepreneurial risk management practices were not fully adopted by SMEs managers for their business operations in Anambra State, Nigeria. It was recommended among others that SMEs managers should establish various entrepreneurial risk management practices levels which will help for sustainability, development and smooth running of their businesses.
Keywords: Small and Medium Scale Entrepreneurs; Entrepreneurial Risk Management Practices